P868 Clinical features of chronic enteropathy associated with SLCO2A1 gene. (30th January 2023) - Umeno, J; Fuyuno, Y; Torisu, T; Matsuno, Y; Esaki, M; Yanai, S; Ohmiya, N; Hisamatsu, T; Watanabe, K; Hosoe, N; Ogata, H; Hirai, F; et al.
Abstract: Background: Chronic enteropathy associated with the SLCO2A1 gene (CEAS) is a hereditary disease caused by mutations of the SLCO2A1 gene which encodes a prostaglandin transporter. This disease is rare and intractable characterized by persistent blood and protein loss. There are few reports from Europe, and most reports are from Asian countries such as South Korea, China, and Japan. Because CEAS and Crohn's disease (CD) present ileal ulcers and stenoses, it is often difficult to distinguish CEAS from CD. Evaluation of characteristic upper gastrointestinal lesions observed in CEAS and extraintestinal findings, such as digital clubbing, periostosis, and pachydermia, can trigger suspicion of this disease, and genetic testing can be performed to confirm the diagnosis. Since little is known about the clinical features of CEAS, we conducted a nationwide survey in Japan. Methods: All study participants provided written informed consent for genetic analysis. The present study was approved by the ethics committee of each institution. During the period between 2012 and 2022, 188 patients suspected of CEAS were enrolled in this study and checked to have SLCO2A1 gene mutations. We reviewed the clinical information of genetically confirmed CEAS patients. Results: We confirmed the genetic analysis of 69 CEAS patients (24 males and 45 females) and found 19 different types of SLCO2A1 mutations. The median age at disease onset and diagnosis was 19 (range 1-69) and 42 (range 7-70) years, respectively. Parental consanguinity was present in 19 patients (26%). Although anaemia was present in almost all patients, only two patients experienced gross haematochezia. The median haemoglobin and serum total protein levels at diagnosis were 9.7 (range 2.3-14.4) and 5.3 (2.7-8.2) g/dl, respectively. Thirty-seven patients (54%) had undergone intestinal surgery. The most frequently involved gastrointestinal site was the ileum (94%), but the terminal ileum was rarely involved (4%). The lesions were shallow ulcers, varying in shape from circular, oblique, to longitudinal, sometimes forming pseudodiverticulum or luminal stenosis. The Gastric lesions were observed in 15 patients (22%) and duodenal lesions in 30 patients (43%). 20 patients (30%) had either mild digital clubbing, periostosis, or pachydermia. The extraintestinal findings, were more frequently found in males than in females (digital clubbing 52% vs 9%; periostosis 50% vs 10%; pachydermia 57% vs 0%). Conclusion: Examination of the clinical features of CEAS reveals that ileal lesions are uniform and characteristic, but clinical features are diverse. Thirty per cent of patients with CEAS have extraintestinal features. There is a significant gender difference in extraintestinal features in CEAS patients.